190k views
4 votes
Solve the system of equations 3x-6y=-393x−6y=−39 and -3x+4y=9−3x+4y=9 by combining the equations.

1 Answer

1 vote

Answer:

(x, y) = (17, 15)

Explanation:

Adding the two equations gives ...

(3x -6y) +(-3x +4y) = (-39) +(9)

-2y = -30

y = 15

__

Substituting this value of y into the second equation, we get ...

-3x +4(15) = 9

-3x = -51

x = 17

The solution is (x, y) = (17, 15).

User Amit Hagin
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.